2020
DOI: 10.3389/fped.2020.567895
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Liver Transplantation in Homozygous Familial Hypercholesterolemia (HoFH)—Long-Term Follow-Up of a Patient and Literature Review

Abstract: Homozygous familial hypercholesterolemia (HoFH) is a rare inherited metabolic disorder, frequently leading to an early cardiovascular death if not adequately treated. Since standard medications usually fail to reduce LDL-cholesterol (LDL-C) levels satisfactorily, LDL-apheresis is a mainstay of managing HoFH patients but, at the same time, very burdensome and suboptimally effective. Liver transplantation (LT) has been previously shown to be a promising alternative. We report on a 14 year-long follow-up after LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 76 publications
0
8
0
2
Order By: Relevance
“…This occurred in spite of the introduction of atorvastatin 3–4 weeks after transplantation [ 23 ]. A recent case report from Slovenia described a 16-year-old patient with HoFH who underwent a deceased donor liver transplant with LDL-C levels up to 449 mg/dL (11.6 mmol/L) on LA and atorvastatin [ 25 ]. The response to liver transplant (LDL-C reduced to 201 mg/dL) (5.2 mmol/L) prompted the medical team to stop the statin and LA; however, the patient had to undergo a course of steroids for an episode of acute rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This occurred in spite of the introduction of atorvastatin 3–4 weeks after transplantation [ 23 ]. A recent case report from Slovenia described a 16-year-old patient with HoFH who underwent a deceased donor liver transplant with LDL-C levels up to 449 mg/dL (11.6 mmol/L) on LA and atorvastatin [ 25 ]. The response to liver transplant (LDL-C reduced to 201 mg/dL) (5.2 mmol/L) prompted the medical team to stop the statin and LA; however, the patient had to undergo a course of steroids for an episode of acute rejection.…”
Section: Discussionmentioning
confidence: 99%
“…LDL-C levels never reached recommended targets for patients with HoFH and remained at more than double that level (approx. 160–200 mg/dL; 4.1–5.2 mmol/L), with the LDL-C levels continuously increasing at the time of the report (14.5 months post-transplant) [ 25 ]. In the case series presented here, only two of the surviving patients were able to achieve EAS guideline targets for LDL-C in patients with HoFH, and only one of these did so without additional support from standard LLTs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that the incidence of homozygotic FH is 1 in 1,000,000, while HeFH is 2000 times more frequent (1:500) [ 49 ]. LT is considered to be a gold standard treatment, but it is invasive and may cause other complications [ 50 ]. LDL apheresis is another therapeutic option, limited due to high costs and difficulty to apply [ 51 ].…”
Section: Familial Hypercholesterolemiamentioning
confidence: 99%
“…ECG signs of subendocardial ischemia (ST segment depression at 7-8 mm) during a dosed exercise test in a child with homozygous hypercholesterolemia (own observations). В ПОМОЩЬ ПРАКТИЧЕСКОМУ ВРАЧУ случаев удается остановить дальнейшее развитие атеросклеротического поражения сердечно-сосудистой системы, в 24,4% отмечается прогрессирование атеросклеротического процесса и только в 12,3% происходит регресс атеросклероза (ксантом и атеросклеротических бляшек в сосудах) [37]. Ограничения трансплантации печени: необходимость постоянной иммунносупрессивной терапии и возможные послеоперационные осложнения [36,37].…”
Section: диагностикаunclassified
“…В ПОМОЩЬ ПРАКТИЧЕСКОМУ ВРАЧУ случаев удается остановить дальнейшее развитие атеросклеротического поражения сердечно-сосудистой системы, в 24,4% отмечается прогрессирование атеросклеротического процесса и только в 12,3% происходит регресс атеросклероза (ксантом и атеросклеротических бляшек в сосудах) [37]. Ограничения трансплантации печени: необходимость постоянной иммунносупрессивной терапии и возможные послеоперационные осложнения [36,37]. В случае выраженного атеросклеротического процесса в сердце (коронарный атеросклероз, поражения аортального клапана) осуществляется комбинированная трансплантация сердца и печени [34,35].…”
Section: диагностикаunclassified